Decision support tools in city planning: bridging the gap between numerologists and conversationalists - Scheurer, Jan; McLeod, Sam; Curtis, Carey (2019)
Decisions taken on transport infrastructure and urban form often rely upon conventional urban models and their interface with Cost-Benefit Analysis. Such positivist methods typically conceal the full complexity and uncertainty of how large projects can transform cities. Recent years have seen the emergence of new, more participatory planning Decision Support Tools (DST), designed to guide broader discussion and facilitate more open and inclusive dialogue between planners and communities. However, the effectiveness of such tools, in informing different political discussions and in ultimately influencing policy outcomes remains poorly understood. This is particularly as participant attention often reverts to system outputs at the expense of discussions of broader goals or strategies. DSTs may also lack ready interoperability with formal project evaluation processes (such as the Infrastructure Australia Assessment Framework), limiting their usefulness in translating future visions into project definition.